2010
DOI: 10.1074/jbc.m109.062844
|View full text |Cite
|
Sign up to set email alerts
|

The Thioredoxin-Thioredoxin Reductase System Can Function in Vivo as an Alternative System to Reduce Oxidized Glutathione in Saccharomyces cerevisiae

Abstract: Cellular mechanisms that maintain redox homeostasis are crucial, providing buffering against oxidative stress. Glutathione, the most abundant low molecular weight thiol, is considered the major cellular redox buffer in most cells. To better understand how cells maintain glutathione redox homeostasis, cells of Saccharomyces cerevisiae were treated with extracellular oxidized glutathione (GSSG), and the effect on intracellular reduced glutathione (GSH) and GSSG were monitored over time. Intriguingly cells lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Regarding this latter issue, it is relevant to mention that in some GR-less organisms, such as Drosophila melanogaster, GSSG reduction is carried out by Trx, which in turn is recycled by TR (12). This is also the case of Saccharomyces cerevisiae null mutants in GR, where the Trx system compensates for the lack of GR activity (13). In this study we present two major findings.…”
mentioning
confidence: 53%
“…Regarding this latter issue, it is relevant to mention that in some GR-less organisms, such as Drosophila melanogaster, GSSG reduction is carried out by Trx, which in turn is recycled by TR (12). This is also the case of Saccharomyces cerevisiae null mutants in GR, where the Trx system compensates for the lack of GR activity (13). In this study we present two major findings.…”
mentioning
confidence: 53%
“…Simultaneous inhibition of more than one antioxidant system for cancer therapy becomes even more important with the growing evidence that the two key redox systems display widespread redundant functions (35,50). Recently, we showed that the cystine/cysteine cycle along with Txnrd1 cooperatively rescue GSH deficiency (35).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive deletion analyses in yeast have further identified considerable genetic redundancy in these systems Toledano et al 2007;López-Mirabal and Winther 2008). The thioredoxin system has also been shown to function as an alternative reduction system for GSSG, although the physiological significance of this reduction reaction is not yet clear (Tan et al 2010). The reason(s) for this apparent functional redundancy in highly conserved redox systems remains an important unanswered question.…”
Section: Cellular Responses To Rosmentioning
confidence: 99%